Neuroinflammation and complexes of 17β-hydroxysteroid dehydrogenase type 10--amyloid β in Alzheimer's disease - Krištofiková, Zdena; Řípová, Daniela; Bartoš, Aleš; Bocková, Markéta; Hegnerová, Kateřina; Řičný, Jan; Čechová, Linda; Vrajová, Monika; Homola, Jiří (Current Alzheimer research, 2013)
Multifunctional mitochondrial enzyme 17β-hydroxysteroid dehydrogenase type 10 plays a role in the development of Alzheimer's disease. However, changes in its expression in the brain or cerebrospinal fluid are not fully specific for this type of dementia. Our previous study revealed that complexes of the enzyme and amyloid β in cerebrospinal fluid could serve as a more specific biomarker of Alzheimer's disease than either the enzyme or amyloid β individually when compared to autoimmune multiple sclerosis. In this study, enzyme-linked immunosorbent assay and the surface plasmon resonance biosensor method were used to analyse cerebrospinal fluid of patients with various neuroinflammatory diseases. Significant differences in the levels of the total enzyme, complexes, amyloid β 1-42 and total τ/phospho-τ were found in Alzheimer's disease patients while differences in complexes, total amyloid β and amyloid β 1- 42 were observed in patients with neuroinflammatory diseases (except for multiple sclerosis) when compared to non-neuroinflammatory controls. The interactions of the enzyme with amyloid β appeared to depend strongly on neuroinflammation-sensitive amyloid β. Our data demonstrated that oligomerisation/aggregation of intracellular amyloid β peptides was important in Alzheimer's disease while extracellular amyloid β could play a role in neuroinflammatory diseases. Phospho-τ is currently the best biomarker of Alzheimer's disease.
Keywords: Surface Plasmon Resonance; Enzyme-Linked Immunosorbent Assay; zánět; Female; povrchová plasmonová rezonance; Amyloid beta-Peptides; Central Nervous System Diseases; Peripheral Nervous System Diseases; ženské pohlaví; lidé; amyloidní beta-protein; Vascular Diseases; peptidové fragmenty; Inflammation; 17-hydroxysteroidní dehydrogenasy; neparametrická statistika; nemoci cév; ELISA; Male; Peptide Fragments; Aged; nemoci centrálního nervového systému; Alzheimer Disease; Alzheimerova nemoc; 17-Hydroxysteroid Dehydrogenases; Statistics, Nonparametric; senioři; mužské pohlaví; nemoci periferního nervového systému; Humans